2009
DOI: 10.1073/pnas.0811486106
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of atmospheric aerosols on marine phytoplankton

Abstract: Atmospheric aerosol deposition is an important source of nutrients and trace metals to the open ocean that can enhance ocean productivity and carbon sequestration and thus influence atmospheric carbon dioxide concentrations and climate. Using aerosol samples from different back trajectories in incubation experiments with natural communities, we demonstrate that the response of phytoplankton growth to aerosol additions depends on specific components in aerosols and differs across phytoplankton species. Aerosol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
335
5
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 366 publications
(372 citation statements)
references
References 38 publications
15
335
5
3
Order By: Relevance
“…Merged satellite chlorophyll (Chl) data were used as an indicator of total phytoplankton biomass (18). Daily Chl variations (ΔChl) were calculated during Cu pulses, as the toxic response of phytoplankton to Cu was previously shown to be evident already on the first day of a Cu event (9,10,19). As seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Merged satellite chlorophyll (Chl) data were used as an indicator of total phytoplankton biomass (18). Daily Chl variations (ΔChl) were calculated during Cu pulses, as the toxic response of phytoplankton to Cu was previously shown to be evident already on the first day of a Cu event (9,10,19). As seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, bioassay experiments have demonstrated that the addition of aerosols containing high copper concentrations to ocean water samples can have detrimental effects on phytoplankton communities (10). Nonetheless, the bulk oceanic response to Cu aerosol deposition has only been assessed based on a coupled atmosphere-ocean model (10). This lack of direct evidence is in itself a cause for major concern because human activities have increased the amount of atmospheric aerosols and specifically those carrying Cu and other metals (11,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[122] Conversely, ship fuels contain high levels of heavy metals, many of which are toxic, which may influence biodiversity and productivity of marine ecosystems. [92] A full assessment of the effect of ship emissions on ocean biogeochemistry, including the effect of nutrient v. toxin input, has yet to be undertaken but coordination with the Atmospheric Nutrient and Oceanderived Aerosols research strategies (see previous two sections) will assist in the development of this emerging SOLAS research theme.…”
Section: Atmospheric Nutrient Supply To the Surface Oceanmentioning
confidence: 99%
“…Cu and Pb). [90][91][92] Consequently deposition represents an important source of new nutrients and particles for large regions of the open ocean. [90,91] This deposition is being perturbed directly and indirectly by anthropogenic activities; for example, atmospheric pollution has greatly increased the deposition of nitrogen, [7] and the magnitude of dust deposition to the oceans has been shown to be climate dependent.…”
Section: Atmospheric Nutrient Supply To the Surface Oceanmentioning
confidence: 99%